1977
DOI: 10.2466/pms.1977.45.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Backward Recognition Masking in Relative Pitch Judgments

Abstract: Backward recognition masking refers to interference of a second masking tone with recognition of a target tone presented earlier in time. The degree of interference has been found to decrease as the length of the silent interval separating the two tones increases. These results have been interpreted as representing interference of the masking tone upon the preperceptual storage and perceptual resolution of the target. It is logically possible, however, that the masking tone does not interfere with perceptual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…These results are largely predictable from the model presented here. The monotonic increase in accuracy with increases in stimulus duration and lSI can be described directly by Equation 1. More important, the increase in perceived duration for the form stimuli with increases in processing time replicates the current results and can be interpreted in a similar manner.…”
Section: Discussionsupporting
confidence: 60%
“…These results are largely predictable from the model presented here. The monotonic increase in accuracy with increases in stimulus duration and lSI can be described directly by Equation 1. More important, the increase in perceived duration for the form stimuli with increases in processing time replicates the current results and can be interpreted in a similar manner.…”
Section: Discussionsupporting
confidence: 60%
“…Hence, it seems clear that in both of our conditions the initial rise of d′ stemmed from a deleterious effect of S2 on the perception of S1 rather than from a deleterious effect of S1 on the perception of S2. Presumably, as Massaro and Idson (1977) suggested in their related study, optimal perceptual processing of S1 was not possible when S2 occurred soon after it. But why did the perceptual processing of S1 require a longer duration in the 30-cycles condition than in the 6-cycles condition?…”
Section: Discussionmentioning
confidence: 78%
“…Several hundreds of milliseconds also seem to be needed for the optimal discrimination of formant transitions in synthetic syllables, according to Pisoni (1973). Finally, in the domain of pitch, an effect of the same type was reported by Massaro and Idson (1977). Their stimuli were 20-msec bursts of sinusoids differing in frequency and, as in Sorkin's study, the two stimuli used on a given trial were presented either to the same ear or to opposite ears.…”
mentioning
confidence: 87%
“…Demany, Montandon, and Semal (2005) found that frequency discrimination between two sequentially presented brief tones actually improved as the ISI between them increased from 0 to approximately 500 ms, and then deteriorated only for longer ISIs. The former effect could be related to a reduction in backward recognition masking as ISI increases beyond 0 ms (Massaro, 1975; Massaro & Idson, 1977). Based on this finding, the difficulty experienced by our participants in the Sequential condition could be because the tones are presented directly after one another, rather than because of a decay in the memory trace between the time of the first and second pitch estimates.…”
Section: Discussionmentioning
confidence: 99%